The siren song remains the same: cult recruitment: tactics and rhetoric - Homeniuk, Emily; Hutchinson, Heather (My University, 2024)
Stories of cults, particularly those fueled by accounts of violence, have captivated the public throughout history. Beyond the fascination with high-profile cases lies a genuine curiosity about the factors that lead people to join and remain in cults. Particularly interesting are the methods cults use to persuade their followers to embrace self-annihilation willingly. While communication’s role in cult recruitment may seem obvious, it remains an unexplored realm of study. Therefore, this research sought to shed light on the communication and rhetorical strategies employed by established cults like the Peoples Temple (Moore, 2013), the Branch Davidians (Rifkind & Harper, 1994), and Heaven’s Gate (Robinson, 1997), compared to the tactics employed by the self-help organization Teal Eye LLC (Swan, 2020). By examining the details and impact of Teal Eye LLC’s (Swan, 2020) communication methods, the study aimed to determine if this organization employs a cult-like stratagem. This research employed historical, content, and critical discourse analysis to determine what communication tactics cults use to attract and retain followers. Moreover, this investigation addressed the scarcity of research and the strength of virtual connections in contemporary cult dynamics, considering the influence of digital platforms and online interactions.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: cults; recruitment; communication methods